Serum levels of monocyte chemotactic protein-3/CCL7 are raised in patients with systemic sclerosis: association with extent of skin sclerosis and severity of pulmonary fibrosis. Issue 1 (12th December 2005) - Yanaba, K; Komura, K; Kodera, M; Matsushita, T; Hasegawa, M; Takehara, K; Sato, S
Abstract : Objective: To determine serum levels of monocyte chemotactic protein-3 (MCP-3) and its clinical associations in patients with systemic sclerosis (SSc). Methods: Serum MCP-3 levels from 69 patients with SSc were examined by ELISA. Results: Serum MCP-3 levels were raised in patients with SSc (n = 69) compared with healthy controls (n = 28). Patients with diffuse cutaneous SSc (n = 36) had higher levels of serum MCP-3 than those with limited cutaneous SSc (n = 33). Patients with raised MCP-3 levels had pulmonary fibrosis and decreased vital capacity (VC) more often than those with normal MCP-3 levels. MCP-3 levels correlated positively with the extent of skin fibrosis, and inversely with %VC and carbon monoxide transfer factor (Tlco ) in patients with SSc. Conclusion: MCP-3 levels were increased in patients with SSc, and correlated with the extent of skin sclerosis and the severity of pulmonary fibrosis. These results suggest that MCP-3 may have a role in the development of fibrosis in SSc.